A New Uniform Format for 360 VR Videos. (24th October 2018) - Guo, J.; Pei, Q. K.; Ma, G. L.; Liu, L.; Zhang, X. Y.
Abstract: Recent breakthroughs in VR technologies, especially in economic VR headsets and massive smartphones are creating a fast‐growing demand for 3D immersive VR content. 360 VR videos record a surrounding environment in every direction and give users a fully immersive experience. Thanks to a ton of 360 cameras that launched in the past years, 360 video content creation is exploding and 360 VR videos are becoming a new video standard in the digital industry. When ERP and CMP are perhaps the most prevalent projection and packing layout for storing 360 VR videos, they have severe projection distortion, internal discontinuous seams or disadvantages in aspect ratio. We introduce a new format for packing and storing 360 VR videos using two stage mappings. Hemispheres are seamlessly and uniformly mapped onto squares. Two respective squares are stitched to form a rectangle with the aspect ratio 2:1 . Our approach is able to avoid internal discontinuity and generate uniform pixel distribution, while keeping the aspect ratio close to the majority standard aspect ratio of 16 : 9 .